1997
DOI: 10.1021/om961052t
|View full text |Cite
|
Sign up to set email alerts
|

Organotantalum Bis(amidinate) Complexes:  Synthesis and Characterization of Methyl, Methylidene, Benzyl, and Imido Derivatives

Abstract: A new series of tantalum complexes incorporating bis(trimethylsilyl)benzamidinate ligands has been prepared and fully characterized; examples include species with alkyl, alkylidene, and imido functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 33 publications
2
43
0
1
Order By: Relevance
“…212 The strategy has been widely use to access tantalum methylidene complexes. 213 More recently, Mindiola reported two elegant and related examples in which deprotonation of Ta-CH3 214 (Scheme 37a) and Nb-CH3 215 groups are effected by ylide Ph3P(CH2). Less common is the intermolecular hydride abstraction from a TM-CH3, which was recently described by our group after adding a salt of the trityl cation as hydride abstractor to [(PONOP)Ir(CH3)] 3.22 (PONOP = 2,6-bis(di-tert-butylphosphinito)-pyridine) (Scheme 37b).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 99%
See 1 more Smart Citation
“…212 The strategy has been widely use to access tantalum methylidene complexes. 213 More recently, Mindiola reported two elegant and related examples in which deprotonation of Ta-CH3 214 (Scheme 37a) and Nb-CH3 215 groups are effected by ylide Ph3P(CH2). Less common is the intermolecular hydride abstraction from a TM-CH3, which was recently described by our group after adding a salt of the trityl cation as hydride abstractor to [(PONOP)Ir(CH3)] 3.22 (PONOP = 2,6-bis(di-tert-butylphosphinito)-pyridine) (Scheme 37b).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 99%
“…Deprotonation of the methyl ligand typically requires the use of a strong base, although milder bases have been reported to react in the gas phase . The strategy has been widely used to access tantalum methylidene complexes . More recently, Mindiola reported two elegant and related examples in which deprotonation of Ta−CH 3 (Scheme a) and Nb−CH 3 groups are effected by the ylide Ph 3 P(CH 2 ).…”
Section: Reactivitymentioning
confidence: 99%
“…Previous work has shown that early metal acyl fragments possess significant oxy-carbene character due to the oxophilicity of the d 0 systems (see refs 8-10)…”
Section: Referencesmentioning
confidence: 99%
“…Benzamidinato complexes of tantalum are accessible by analogous routes. [195] The starting material of choice is again Me 3 TaCl 2 .…”
Section: Compounds With Metals In the High Oxidation State And The Anmentioning
confidence: 99%